STUDI KETAHANAN ELEMEN STRUKTUR BALOK DAN PELAT GEDUNG PERKANTORAN DENGAN USIA LAYAN 40 TAHUN - Asiya Nurhasanah Habirun (Ensiklopedia of Journal, 2021)
An office building in Gatot Subroto-Central Jakarta has been built since 1974. It is possible that the existing structure of the building has weakened considering that it is more than 40 years old. The stages of the structural strength study include visual inspection, field inspection, and structural analysis based on existing conditions. The condition of the beam elements from visual observations has cracked at several points and the quality of the concrete from the hammer test results ranges from 23.27 MPa to 40.37 MPa. The floor covering has been replaced for 2 (two) times without peeling the original layer, the slab elements have low quality ranging from 10.26 to 19.06 MPa. This condition provides an excess ratio or excess capability to the slab structural elements which results in the reduction of the beam structural elements to withstand the load at several points.